CLINICO-RADIOLOGICAL PARAMETERS OF THE PATELLOFEMORAL JOINT IN MALES AND FEMALES WITH NON-PATELLOFEMORAL KNEE PROBLEMS: A COMPARATIVE ANALYSIS - CHANDRA, SHASHANK; REHAN-UL-HAQ; CHAUDHARY, MALAY; AGGARWAL, ADITYA NATH (International Journal of Current Pharmaceutical Research, 2023)
Objective: Osteoarthritis of the knee joint is a common condition that primarily affects the elderly. While previous studies have focused on the tibiofemoral compartment, the significance of the patellofemoral compartment needs to be considered. Patellofemoral joint problems frequently occur in orthopedics and sports medicine and can be challenging to diagnose. Various classification systems have been developed to categorize patellofemoral pathology. Clinical evaluation, as well as imaging techniques such as X-rays and computed tomography (CT), are commonly used for assessment. However, there is a lack of published studies defining and validating MRI parameters for routine clinical assessment of patellofemoral joint abnormalities. Methods: This comparative analytical study was conducted at the Department of Orthopedics, UCMS and GTB Hospital, Delhi, from November 2017 to April 2019. The sample size included 30 male and 30 female participants between the ages of 18 and 45 y. The study evaluated various clinical, radiographic, and MRI parameters of the patellofemoral joint in both males and females. Statistical analysis was performed to determine any significant differences between the genders. Results: The clinical evaluation revealed a slightly higher mean Q angle in females compared to males, although this difference was not statistically significant. Lateral radiographs showed a significant difference in the Insall-Salvati ratio between genders, while the modified Insall-Salvati ratio and Caton-Deschamps index did not show significant differences. MRI measurements demonstrated a significant difference in the I/S ratio between males and females, while other parameters did not exhibit significant gender differences. Conclusion: This study provides valuable insights into the differences in clinical, radiographic, and MRI parameters of the patellofemoral joint between adult males and females. The findings suggest that gender differences exist in certain measurements, emphasizing the need for gender-specific evaluation. Further research is required to explore the clinical implications of these differences and to establish normative values for MRI parameters in routine clinical practice.